(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The future of labour is a complex and multifaceted phenomenon fashioned by rapid technological improvements, demographic shifts, and societal changes. This complete evaluate paper explores the transformative forces reshaping the work panorama, delving into key developments, challenges, and possibilities.